Factors of Family Communication in Forming Children's Personality - Hafni, Rayni Delya; Putri, K. Y.S. (Universitas Veteran Bangun Nusantara, 2022)
Family communication that exists is very important in the personality of the child. Therefore, the patterns of communication and interaction carried out by a family are of great concern. The purpose of this study was to read and analyze and find answers to problems in family communication in shaping children's personalities. This research uses family communication factors variables which have four dimensions, namely communication sources, messages, media, and recipients. The approach in this research is a quantitative approach with a descriptive research type. Population and sample stated 34 people who are elementary school students. The results showed that something was lacking in the factors of family communication carried out by their families. This can be seen in the lowest intentions, namely messages with scientific indicators, while the communication that occurs face-to-face to their families is maximized.